Express 4x/(x^2-9) - 2/(x+3) as a single fraction in its simplest form.

To satisfy the condition of substracting two fractions with unlike denominators, a common denominator needs to be found. By recognizing x^2 - 9 = (x-3)(x+3), we can rewrite the question as 4x/(x-3)(x+3) - [2/(x+3)] * [(x-3)/(x-3) ]= [4x-2(x-3)]/[(x+3)(x-3)] = 2(x+3)/(x+3)(x-3) = 2/(x-3)The answer is 2/(x-3).

Answered by Ye C. Maths tutor

5492 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A curve has the equation: x^4 + 2x -xy - y^3 - 10=0. Find dy/dx in terms of x and y.


d/dx ( sin x) ^3


Using partial fractions, find f(x) if f'(x)=5/(2x-1)(x-3)


How can I find the area under the graph of y = f(x) between x = a and x = b?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences